Vaccination Rate and Seroepidemiology of Hepatitis A in Chronic-Hepatitis-B-Infected Individuals in the Korean Army (Gut and Liver, 2010)
Background/Aims: Vaccination against hepatitis A virus (HAV) is recommended for patients with chronic hepatitis B (CHB), since they are potentially at an increased risk of HAV-related morbidity and mortality. However, little is known about the adherence to these recommendations in the community. This study evaluated the current vaccination status and immunity against HAV among Korean military soldiers with CHB. Methods: We performed a prospective study of Korean military soldiers from August 2008 to January 2009. We enrolled 96 soldiers with CHB on a consecutive basis. We assessed their vaccination history and the presence of anti-HAV immunoglobulin G (IgG). Results: The HAV vaccination rate of the soldiers enrolled in our study was 2% (2 of the 96 soldiers). The seroprevalence rates of anti-HAV IgG among military soldiers without a vaccination history were 0%, 50%, and 100% for those aged 19-29 years (n=71), 30-39 years (n=8), and 40 years or older (n=15), respectively (p＜0.001). Conclusions: The HAV vaccination rate is very low among military soldiers. Public health efforts aimed at raising awareness about HAV vaccination in patients with CHB should be strongly encouraged. (Gut Liver 2010;4:207-211)